Intermediate Joomla CMS version 3.x - Vivante, Ben.; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course is designed to assist students responsible for building and maintaining both internal and external websites. Over training will cover in depth the Joomla Content Management System, from installation up to building a website."--Resource description page.
Title from title screen.
Publication information from resource description page.
Presenter, Ben Vivante.
Keywords: Joomla! (Computer file); Web sites -- Authoring programs; Web site development; Electronic books